The rebirth of Orthodoxy signs of new life in Christianity - Oden, Thomas Clark, 1931- (San Fransisco, CA Harper Collins, 2003)
Includes bibliographical references and index.
Keywords: Postmodernism -- religious aspects -- Christianity; Theology